Effectiveness and safety of ustekinumab for the treatment of psoriasis; six years of clinical experience - Melis Gönülal; Didem Didar Balcı; Aylin Öztürk; Sinan Doğan (Taylor & Francis Group, 2023)
Background This work aimed to investigate the long-term clinical experience with ustekinumab in cases with psoriasis. Materials and methods This retrospective cohort research group consisted of cases who presented to the dermatology outpatient clinics between January 2015 and January 2021, diagnosed with psoriasis, and were treated with ustekinumab. Data including gender, age, weight, disease duration, naïve and non-naïve status, psoriasis type, duration of medication, comorbidities, psoriasis area and severity index scores, the causes of treatment discontinuation, and previous treatments were retrospectively reviewed and analyzed. Results 160 cases with psoriasis were treated with ustekinumab during the research period. Twenty-four patients were excluded. Among 136 cases, 84 (61.8%) were male and 52 (38.2%) were female. We determined 80.55% of the non-naïve cases responded to ustekinumab. Conclusion Ustekinumab can be a suitable treatment option for non-naïve and resistant patients. Our data suggest the positive effect persists in cases with favorable responses to the first or second dose of ustekinumab. Also, we determined male cases gave more rapid and more robust responses than female cases, and patients were more willing about continuing the treatment.